An interpretive model for the double peaks of divertor tungsten erosion during type-I ELMs in EAST. (28th June 2021) - Xu, Guoliang; Ding, Rui; Ding, Fang; Chen, Xiahua; Qian, Xinyuan; Brezinsek, Sebastijan; Gao, Xiang; Zang, Qing; Wang, Liang; Jie, Yinxian; Yan, Peiguang; Chen, Junling; et al.
Abstract: Double peaks of divertor tungsten erosion during type-I edge-localized modes (ELMs) were observed in the EAST tokamak. To study this unique phenomenon, an analytical model of plasma expansion into vacuum was used to investigate the ELM parallel transport along the magnetic field line to the divertor target. The modeling results reveal that during ELM bursts, the energetic C 6+ transport is slower than the main ions due to a lower initial thermal speed. The time of C 6+ arriving at the divertor target from the modeling is consistent with the second tungsten erosion peak. Based on the particle flux from the transport model, a newly developed mixed-material model quantitively reproduced the intra-ELM tungsten erosion profiles for both deuterium and helium discharges. A lithium–carbon coating makes the heavier impurity (C 6+ ) comparatively more effective than the main ions on tungsten sputtering, and thus makes the second tungsten erosion peak more remarkable on EAST experiments.